2008
DOI: 10.1155/2008/784313
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia‐Modified albumin level in type 2 diabetes mellitus—Preliminary report

Abstract: Aim: The main goal of the present study was the evaluation of ischemia-modified albumin (IMA) in patients with type 2 diabetes mellitus and estimation of its connection with vascular complications, glycemic control, hypertension, dyslipidemia and obesity. Methods: In 76 diabetic patients and 25 control subjects, a plasma level of IMA by manually performed, spectrophotometric Co(II)-albumin binding assay was determined. Other parameters such as glucose, fructosamine, HbA1c, total cholesterol and its fractions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
90
2
7

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 32 publications
(50 reference statements)
10
90
2
7
Order By: Relevance
“…17 Similarly we anticipated that IMA levels will be elevated in HCV (+) HD patients, as few studies have advocated that there is a modification of albumin in both acute and chronic oxidative stress leading to elevated IMA levels. 18,19 But on the contrary we did not find any further significant increase in IMA levels in HCV (+) HD patients when compared to HCV (-) HD patients. Bilirubin is a well known antioxidant and when bound to human albumin scavenges free radical thereby protecting albumin bound fatty acids and most likely the protein itself from oxidation.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…17 Similarly we anticipated that IMA levels will be elevated in HCV (+) HD patients, as few studies have advocated that there is a modification of albumin in both acute and chronic oxidative stress leading to elevated IMA levels. 18,19 But on the contrary we did not find any further significant increase in IMA levels in HCV (+) HD patients when compared to HCV (-) HD patients. Bilirubin is a well known antioxidant and when bound to human albumin scavenges free radical thereby protecting albumin bound fatty acids and most likely the protein itself from oxidation.…”
Section: Discussioncontrasting
confidence: 88%
“…However it is being revealed that IMA levels do rise in conditions not related to cardiac ischemia such as in diabetes 6 , ESRD 13 and HD. 11 Although studies have reported elevated IMA levels in ESRD patients 10,11,14 the impact of HCV infection on IMA levels in HD patients has not been explored further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IMA may not be specific for cardiac ischemia. There are various data on IMA in patients with different states with ischemia of non-cardiac origin such as systemic sclerosis, peripheral vascular disease, skeletal muscle ischemia, glaucoma and diabetes mellitus Montagnana et al, 2006;Piwowar et al, 2008). Also, serum IMA levels are increased in patients with gastric, prostate, neuroblastoma and soft tissue cancer (Mastella et al, 2009;StachowiczStencel et al, 2011;Fidan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple reports [13][14][15] including ours 12 showed increased lipid peroxidation and impaired antioxidant status in diabetes and DR, little published data on protein markers of OS in both diabetes and DR patients are available. 11,16 Although ischemia modified albumin (IMA) has been demonstrated as a novel marker of ischemia, OS and endothelial dysfunction in diabetes [17][18][19] studies on IMA in DR patients are very scarce. To the best of our knowledge, there is only one study in the literature on IMA levels in human DR patients.…”
Section: Introductionmentioning
confidence: 99%